Analysis of the Health Level of Financial Services State-Owned Enterprises (Study on Insurance Business Field Companies during the Period 2018 - 2022) - Chantika, Shakira Ratu; Zaki, Ahmad; Indarwanta, Didik (Jurnal Administrasi Bisnis, 2025)
This study aims to determine the level of health of SOE financial services companies in the insurance business sector for the period 2018-2022 through financial aspects, operational aspects, and administrative aspects that refer to the Regulation of the Minister of BUMN Number: PER-10 / MBU / 2014. This type of research uses analytical descriptive research with a quantitative approach. This research uses secondary data, namely in the form of company financial reports with collection techniques using documentation studies. The sampling technique used in this research is purposive sampling non-random sampling. The samples used include PT Jasa Raharja, PT Asuransi Kredit Indonesia, and PT Reasuransi Indonesia Utama. The data analysis technique used, namely using the financial statement ratio analysis method which refers to the Regulation of the Minister of BUMN Number: PER-10 / MBU / 2014. The results showed that the health level of BUMN financial services companies in the insurance business sector for the period 2018 - 2022 was at the level of "Less Healthy" BBB category with a score of 63.33.  Based on the results of the analysis, it is known that the company is experiencing poor performance in ROA, ROE, YOI, and company premium growth.